Construction supply chains: analysis and computational simulation - Alves, Thaís da Costa Lago (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper discusses the importance of managing supply chains in the construction industry as well as concepts that may contribute for the improvement of their performance. In order to illustrate the concepts discussed and their importance, the authors present a simulation model developed using data from the HVAC sheet metal ductwork supply chain. Conducting experiments on supply chains can be rather costly and time consuming. Therefore, simulation tools can be employed to carry out low cost studies of supply chains. Those tools can be used for generating models that mimic a controlled environment in which experiments can be carried out. Four scenarios were studied to evaluate the impact that variations on activity durations and batching have on the project lead time. The conclusions highlight the use of simulation as a tool for supply chain and production system design, the need to improve communication channels between different parts of the supply chain aiming to reduce inventories, and the impact that variability and batching have on the project lead time.